Network Structure Predicts Changes in Perception Accuracy of Social Relationships - Daniel, João R.; Silva, Rita R.; Santos, António J. (Frontiers in Psychology, 2018)
The goal of this study was to test how changes in perception accuracy of affiliative networks (i.e., the ability to accurately identify who affiliates with whom) are related to an important structural feature of peer groups- the likelihood of children to affiliate with mutual partners (transitivity). Data from three longitudinal samples (two from elementary school children and one from young adolescents; N = 257, 618 observations) show that children and adolescents in classrooms with a higher proportion of transitive relationships are better at perceiving who affiliates with whom, and that increases in transitivity associate with increases in perception accuracy. This is the first study to show that structural features of peer groups relate with individual perceptions of affiliative relationships, providing further evidence that these features have an important role in promoting individual adaptation and supporting previous suggestions that classroom-variables play a role in fostering accurate perceptions of social relationships.